Sistem Penyewaan Ruang dan Fasilitas Gedung Academic Activity Center (AAC) Dayan Dawood berbasis Web - Kurniawaty, Risma; Irvanizam, Irvanizam; Saputra, Kurnia (Department of Informatics, Universitas Syiah Kuala, 2023)
Syiah Kuala University has the Dayan Dawood Academic Activity Center (AAC) Building as a non-academic business unit that focuses on renting rooms and facilities for various purposes. This building is very often used for various activities, but unfortunately, the rental procedure is still conventional so it is prone to errors and loss of reservation data so the income calculation is not optimal. In addition, price and facility information is not yet accessible to the public. The problem will be solved by creating a website-based information system that can manage the rental of the Dayan Dawood Academic Activity Center (AAC) building with two groups of users, namely admins and tenants. This system was built using the CodeIgniter framework and MYSQL database. The system creation process applies the Scrum method as project management. System testing consists of functionality testing using Black Box Testing and Usability Testing using UMUX-LITE. Black Box Testing has successfully run all test scenarios as they should. Usability Testing was conducted on 29 respondents and resulted in a score of 83.97, the application is in the